Elemental concentration based potential ecological risk (PER) status of the surface sediments, Pulicat lagoon, Southeast coast of India. (August 2018) - Saravanan, P.; Krishnakumar, S.; Pradhap, D.; Silva, Judith D.; Arumugam, K.; Magesh, N.S.; Srinivasalu, S.
Abstract: Eighty-three surface sediments were collected to investigate the element concentration based sediment pollution and potential ecological risk status of the Pulicat lagoon, southeast coast of India. The textural characteristics, Fe and Mn concentration in the surface sediments are chiefly controlled by the confluence of riverine inputs and vicinity of the marine environment. The varied distribution of CaCO3 concentration is due to the depth of the lagoon followed by the sand and silty sand characteristics of the substratum. The surface sediments are derived from riverine sources. Sediment Pollution Index (SPI), Potential Ecological Risk Index of the sediments suggests that they are falling under less polluted and low potential ecological risk category. Highlights: The attempt was carried out to assess the elemental based potential ecological risk status of the Pulicat lagoon. The distribution of CaCO3 was controlled by the available shell fragments. The surface sediment accumulated elements supplied through natural sources except Pb. The sources of the Pb in the sediments is from coal incinerating power plants and application of leaded fuels. The outcome of the present work is addressed that the Pulicat lagoon under low risk category.